2021
DOI: 10.1155/2021/9980137
|View full text |Cite
|
Sign up to set email alerts
|

Early Osteogenic Differentiation Stimulation of Dental Pulp Stem Cells by Calcitriol and Curcumin

Abstract: Curcumin, as a natural phenolic substance, is extracted from the rhizome of Curcuma longa (turmeric), which is effective in bone healthfulness. Calcitriol is an effective hormone in regulating bone remodeling and mineral homeostasis and immune response. Mesenchymal stem cells (MSCs) are found in most dental tissues and resemble bone marrow-derived MSCs. In this work, we investigated the effect of combination and individual treatment of curcumin and calcitriol on early osteogenic differentiation of dental pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Our other recent study showed that curcumin upsurges the early osteogenic differentiation of DPSCs. These outcomes were demonstrated by analyzing the activity of ALP or osteogenic gene expression levels [44]. In another study, the cytotoxicity of curcumin and the osteogenic marker expression in C3H1-T1/2 cells were tested and it was shown that curcumin improved the expression of ALP and osteocalcin (OC) genes that then differentiated osteoblasts in cells [18].…”
Section: Resultsmentioning
confidence: 99%
“…Our other recent study showed that curcumin upsurges the early osteogenic differentiation of DPSCs. These outcomes were demonstrated by analyzing the activity of ALP or osteogenic gene expression levels [44]. In another study, the cytotoxicity of curcumin and the osteogenic marker expression in C3H1-T1/2 cells were tested and it was shown that curcumin improved the expression of ALP and osteocalcin (OC) genes that then differentiated osteoblasts in cells [18].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, CF exhibited an opposite effect on the PI of osteoblasts ( Figures 3A,C,D ). ALP activity is the marker of early osteogenic differentiation ( 49 ). As shown in Figure 3E , the ALP activities of MC3T3-E1 cells treated with MGF and CF for 120 h both highly significantly ( P < 0.01) decreased, which was different from other studies ( 7 , 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin has a wide range of effects for medical application (Ghavimi et al, 2020; Samiei, Abedi, Sharifi, & Maleki Dizaj, 2021; Sharifi et al, 2019; Sharifi, Fathi, et al, 2020; Sharifi, Moghaddam, et al, 2020), which can interact with various molecular targets involved in chronic diseases (Canistro et al, 2021). Curcumin can be an alternative to chemotherapy drugs due to its anticancer properties and low side effects.…”
Section: Introductionmentioning
confidence: 99%